BENTUK PASIF DALAM BAHASA MANGGARAI - , Stephanus Mangga ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The object of this research is about passive voice in bahasa Manggarai (BM). BM is one of the languages in the western part of the mainland of Flores. Genetically, BM belongs to the sub-Malayo-Polynesian family of Central- Austronesian. In terms of morphology, words in BM consist of a single morpheme or are monomorfemik generally. It characterizes BM as an isolation language. Structurally, BM belongs to the SVO-type language. By the SVO type, BM has a deep sentence which Subject is preverbal